2021
DOI: 10.1111/ijcp.14108
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of epidemiology, clinical features, prognosis, diagnosis and treatment outcomes of patients with COVID‐19 in West Azerbaijan Province

Abstract: Background COVID‐19 is considered a widespread concern in global public health. Diagnoses of COVID‐19 in some cases are necessary because of severe prognosis. In this study, epidemiologies, clinical and demographic characteristics of patients with COVID‐19 were studied in Taleghani Hospital, Urmia, Iran. Methods This descriptive‐analytical cross‐sectional study was carried out on 215 patients with COVID‐19 during March and April 2020. Approved COVID‐19 case was considered as a person with a positive respirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Characteristics associatedwiththeseverityofSARS-CoV-2infectionmayallowearly identification and management of patients with poor outcomes; these include clinical factors such as cerebrovascular and cardiovascular disease, chronic obstructive pulmonary disease, diabetes, hypertension, smokingandmalesexandlaboratoryfindingssuchasincreasedprocalcitonin, increased d-dimerandthrombocytopenia. [14][15][16][17] The management of the hospitalised patients is based on clinical, laboratory and imaging data. In particular, chest computed tomography(CT)isoneofthefundamentalexamsforthesuccessivetherapeutic course.…”
Section: Asignificantnumberofinfectedpeopleisasymptomaticwithamentioning
confidence: 99%
“…Characteristics associatedwiththeseverityofSARS-CoV-2infectionmayallowearly identification and management of patients with poor outcomes; these include clinical factors such as cerebrovascular and cardiovascular disease, chronic obstructive pulmonary disease, diabetes, hypertension, smokingandmalesexandlaboratoryfindingssuchasincreasedprocalcitonin, increased d-dimerandthrombocytopenia. [14][15][16][17] The management of the hospitalised patients is based on clinical, laboratory and imaging data. In particular, chest computed tomography(CT)isoneofthefundamentalexamsforthesuccessivetherapeutic course.…”
Section: Asignificantnumberofinfectedpeopleisasymptomaticwithamentioning
confidence: 99%
“…A study by Nabavi et al 5 in the northeast of Iran reported that low O 2 saturation, nausea/vomiting, and extent of lung CT involvement were independent predictors of severe/critical COVID‐19 (OR = 0.342, 45.93, and 25.48, respectively; p < 0.05). On the other hand, a study by Allameh et al 22 in Tehran, Iran, and another study by Gharebaghi et al 23 in the West side of Iran indicated fever (93.59%) and shortness of breath (62.8%) as the most common clinical manifestations of the severe COVID‐19. Interestingly, Sohrabi et al 24 revealed that impaired consciousness could be the most powerful predictor of COVID‐19 severity and mortality (OR = 3.73, 95% CI = 3.508–3.979, p < 0.001); however, they reported decreased O 2 saturation and dyspnea as other significant factors (OR = 2.67 and 1.63, respectively).…”
Section: Discussionmentioning
confidence: 94%
“…respectively; p < 0.05). On the other hand, a study by Allameh et al22 in Tehran, Iran, and another study by Gharebaghi et al23 in the West side of Iran indicated fever (93.59%) and shortness of breath (62.8%) as the most common clinical manifestations of the severe COVID-19.Interestingly, Sohrabi et al24 revealed that impaired consciousness could be the most powerful predictor of COVID-19 severity and T A B L E 5…”
mentioning
confidence: 98%
“…COVID-19 infection, as a global health concern, has led to a severe crisis and a massive number of deaths since the pandemic emergence ( 1 , 2 ). Whilst global vaccination has controlled the soaring rate of afflictions and fatalities in the majority of countries, there is still evidence of new waves of disease transmission in some nations.…”
Section: Introductionmentioning
confidence: 99%